RETRACTED: Early Childhood Education Learning Model in Malaysia - Ahmad Syukri Sitorus; Arifin Muhammad; Dea Putri Jelita; Putri Aulia; Angela Sayfriani; Sahida Binti Zainuddin (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Following a rigorous, carefully concerns and considered review of the article published in Jurnal Obsesi to article entitled